Analyse und Simulation von energieeffizienten Online-Scheduling Algorithmen - Kratzmann, Julian

An Optimization Model for the optimal Usage of Water Tanks in Water Supply Systems - Dohle (married name: Hallmann) , Corinna; Suhl, Leena (Proceedings of the International Conference on Applied Mathematical Optimization and Modelling (APMOD))
In Germany, the optimization of water supply systems has gained more and more attention due to a growing cost pressure for German municipal utilities. In this work, a model is presented which optimizes the usage of water tanks. On the one hand locations of new tanks are identified, and on the other hand the size of existing tanks is optimized, subject to satisfying the demand of clients and providing the necessary amount of fire water during all time periods. The main difficulty is the consideration of the head loss equation which is required to model the hydraulic properties of a water supply system. As this equation is non-convex and quadratic the optimization model becomes a non-convex Mixed Integer Quadratically Constrained Program (MIQCP). To solve this MIQCP different solution methods are applied.

An Algorithm for Facility Leasing - Meyer auf der Heide, Friedhelm; Pietrzyk, Peter; Kling, Peter (Proceedings of the 19th International Colloquium on Structural Information & Communication Complexity (SIROCCO))
We consider an online facility location problem where clients arrive over time and their demands have to be served by opening facilities and assigning the clients to opened facilities. When opening a facility we must choose one of K different lease types to use. A lease type k has a certain lease length lk. Opening a facility i using lease type k causes a cost of f k i and ensures that i is open for the next lk time steps. In addition to costs for opening facilities, we have to take connection costs ci j into account when assigning a client j to facility i. We develop and analyze the first online algorithm for this problem that has a time-independent competitive factor.This variant of the online facility location problem was introduced by Nagarajan and Williamson [7] and is strongly related to both the online facility problem by Meyerson [5] and the parking permit problem by Meyerson [6]. Nagarajan and Williamson gave a 3-approximation algorithm for the offline problem and an O(Klogn)-competitive algorithm for the online variant. Here, n denotes the total number of clients arriving over time. We extend their result by removing the dependency on n (and thereby on the time). In general, our algorithm is O(lmax log(lmax))-competitive. Here lmax denotes the maximum lease length. Moreover, we prove that it is O(log2(lmax))-competitive for many “natural” cases. Such cases include, for example, situations where the number of clients arriving in each time step does not vary too much, or is non-increasing, or is polynomially bounded in lmax.

Alternative Berechnung der Machtindizes: Banzhaf und Shapley-Shubik Index - Dawirs, Friederike

Adaptive Verbindungsstrategien in dynamischen Suchnetzwerken - Eidens, Fabian

A UML-based Rich Service Description for Automatic Service Discovery - Huma, Zille; Gerth, Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the Forum at the CAiSE'12 Conference on Advanced Information Systems Engineering)
Service-oriented computing (SOC) emerges as a promising trend solving many issues in distributed software development. Following the essence of SOC, service descriptions are dened by the service partners based on current standards, e.g., WSDL [15]. However, these standards are mostly structural and do not provide any behavioral description, which may lead to inaccurate service discovery results. There is a requirement for a rich service description language for service partners that encompasses the structural as well as behavioral information in the service description. Furthermore, service discovery based on an automatic matching of these comprehensive service descriptions is a complex task, which is further complicated through the heterogeneity of the service partners' domains in terms of dierent underlying ontologies. In this paper, we propose a rich service description language based on UML, which allows the specication of structural and behavioral features of a service. In addition, we also briefly discuss how some existing matching approaches can be extended to dene an automatic matching mechanism for rich service descriptions resolving the underlying heterogeneity.

A Self-Stabilization Process for Small-World Networks - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of the 26th IEEE International Parallel and Distributed Processing Symposium (IPDPS))
Small-world networks have received significant attention because of their potential as models for the interaction networks of complex systems. Specifically, neither random networks nor regular lattices seem to be an adequate framework within which to study real-world complex systems such as chemical-reaction networks, neural networks, food webs, social networks, scientific-collaboration networks, and computer networks. Small-world networks provide some desired properties like an expected polylogarithmic distance between two processes in the network, which allows routing in polylogarithmic hops by simple greedy routing, and robustness against attacks or failures. By these properties, small-world networks are possible solutions for large overlay networks comparable to structured overlay networks like CAN, Pastry, Chord, which also provide polylogarithmic routing, but due to their uniform structure, structured overlay networks are more vulnerable to attacks or failures. In this paper we bring together a randomized process converging to a small-world network and a self-stabilization process so that a small-world network is formed out of any weakly connected initial state. To the best of our knowledge this is the first distributed self-stabilization process for building a small-world network.

A Forensic Framework for Automatic Information Retrieval in Distributed Systems - Schluessler, Jonathan

Informationen aus der Lehrer- und Schülerbefragung! Eine empirische Studie zu den Erfahrungen von Lehrkräften und Jugendlichen im beruflichen Übergangssystem - Kremer, H.-Hugo; Beutner, Marc; Zoyke, A. (Individuelle Förderung und berufliche Orientierung im berufsschulischen Übergangssystem - Ergebnisse aus dem Forschungs- und Entwicklungsprojekt InLab)

Weiterbildung "Individuelle Förderung in der beruflichen Bildung" - Entwicklungen und Implementation eines Blended Learning Ansatzes im Projekt InLab - Kremer, H.-Hugo; Rhode, S.; Zoyke, A. (Individuelle Förderung und berufliche Orientierung im berufsschulischen Übergangssystem - Ergebnisse aus dem Forschungs- und Entwicklungsprojekt InLab)

Stärkenbasierte Bildungsarbeit zur individuellen Kompetenzentwicklung im Übergang von Schule zu Berufs- und Arbeitswelt - Kremer, H.-Hugo; Knust, S. (Individuelle Förderung und berufliche Orientierung im berufsschulischen Übergangssystem - Ergebnisse aus dem Forschungs- und Entwicklungsprojekt InLab)

Berufsorientierung als Herausforderung für berufsbildende Schulen - Kremer, H.-Hugo (Die berufsbildende Schule)

Didaktische Potenziale des Mobile Learning für die Berufsbildung: Erfahrungen aus einem Pilotprojekt am Center for Young Professionals in Banking in der Schweiz - Seufert, Sabine; Jenert, Tobias; Kuhn-Senn, Andrea (Berufsbildung in Wissenschaft und Praxis)
Mobile Learning liegt in der beruflichen Bildung seit dem Aufkommen von Smartphones, Tablet-PCs1 und speziell entwickelten Applikationen (Mobile Apps) im Trend. Ziel des Beitrags ist es, die didaktischen Potenziale des Mobile Learning durch den Einsatz von Tablet-PCs in der beruflichen Ausbildung zu untersuchen. Als Ausgangspunkt dient dabei das Fallbeispiel des Center for Young Professionals in Banking in der Schweiz, das im Jahr 2011 eine umfassende Pilotstudie durchgeführt hat. Ausgehend vom konkreten Fall werden anschliessend die Potenziale für medienbezogene Kompetenzen sowie eine "didaktische Landkarte" zur Verortung von Mobile-Learning-Szenarien eingeführt, um die verschiedenen pädagogischen Leitvorstellungen dieser Szenarien aufzuzeigen.
Keywords: mobile learning; tablets; tablet learning; mobile technologies; elearning; TEL

Studienprogramme als didaktische Gestaltungs-und Untersuchungseinheit: Theoretische Grundlegung und empirische Analyse - Jenert, Tobias
Mit welchen Erwartungen und Anforderungen sehen sich Studierende im Hochschulalltag konfrontiert? Wie muss nach Ansicht der Studierenden gehandelt werden, um das Studium "erfolgreich" zu bewältigen? Wie laufen die Auswahl unterschiedlicher Lernaktivitäten im Studium sowie die Allokation von Ressourcen im Detail ab? Diese und weitere Fragen sind vor allem im Zusammenhang mit der Debatte um die Bologna-Reform stärker in den Mittelpunkt gerückt. Denn während modularisierte Curricula und Credit-Point-Systeme oft nach administrativ-organisatorischen Gesichtspunkten eingeführt wurden, hat die Gestaltung der Studienstrukturen auf Programmebene zwangsweise Auswirkungen auf das Studienhandeln - und damit auch auf das Lernen der Studierenden. Es gibt viele Vermutungen über die "Wirkungen" von Bologna auf das Studieren: Die Rede ist von Verschulung, Entwissenschaftlichung und Arbeitsüberlastung und Studierende stehen im Verdacht, ihren Studienpfad eher im Sinne einer Credit-Point-Jagd denn interessengeleitet zu gestalten. In der Regel bleibt es dabei jedoch bei anekdotischen Beobachtungen - es fehlt bislang an gesicherten Erkenntnissen über Zusammenhänge zwischen Bologna-konformen Studienkontexten und dem Handeln Studierender. Denn obschon Studierende seit langem Gegenstand der Forschung sind, ist bislang wenig darüber bekannt, wie sie den langfristigen Bildungsprozess eines ganzen Studiums gestalten. Stattdessen wurde vorwiegend das Lernen im engeren Sinne, das so genannte "Classroom Learning" untersucht. Diejenigen, die Studienprogramme nach didaktischen Gesichtspunkten gestalten wollen müssen wissen, wie Studierende mit unterschiedlichen Studienstrukturen umgehen. Denn nur so ist eine planvolle Programmgestaltung im Sinne pädagogischer Zielsetzungen und didaktischer Prinzipien möglich. Die vorliegende Arbeit nimmt diese Problemstellung auf und untersucht, welche Zielvorstellungen und Handlungsstrategien Studierende bei der Bewältigung ihres Studienalltags in unterschiedlichen Bologna-konformen Studienprogrammen entwickeln. Im Einzelnen wird gefragt, (1) welche Vorstellungen, Wahrnehmungen und Handlungslogiken das Handeln Studierender in unterschiedlichen Studienprogrammen prägen und (2) welche programmspezifischen Kontextbedingungen die Herausbildung dieser handlungsleitenden Charakteristika beeinflussen. Ausgehend von diesen beiden Fragestellungen wird zunächst ein theoretisch fundierter Analyserahmen für Studienprogramme entwickelt. Darauf aufbauend werden verschiedene Studienprogramme empirisch untersucht, um schliesslich Design-Prinzipien für die Gestaltung von Studienprogrammen zu formulieren. Es wird nicht davon ausgegangen, dass Studienstrukturen das Handeln Studierender im Sinne eines kausalen Wirkungszusammenhangs bestimmen. Vielmehr wird gefragt, was die Studierenden mit den Strukturen, auf die sie treffen, machen. Studienprogramme werden als kulturelle Einheiten verstanden, innerhalb derer sich spezifische handlungsleitende Vorstellungen und Normen entwickeln. Diese impliziten Regeln des Studienhandelns - das so genannte "Hidden Curriculum" - und vor allem auch die dahinterliegenden Konstruktionsprozesse aufzudecken, ist Ziel dieser Arbeit.
Keywords: Studierverhalten; Hochschuldidaktik; Lernpsychologie; Kulturpsychologie; Bologna-Prozess; Curriculumentwicklung; Hochschulbildung; Study programme; Bologna-process; educational development; cultural psychology; higher education; curriculum development

Status Quo von Hochschuldidaktik/-entwicklung: Erhebung im Herbst 2011 - Brahm, Taiga; Jenert, Tobias
Keywords: Hochschulentwicklung; Hochschuldidaktik

Studienprogramme als hochschuldidaktische Gestaltungs-und Untersuchungseinheit - Jenert, Tobias
In den vergangenen Jahren wurden viele Vermutungen über die "Wirkungen" von Bologna auf das Studieren geäussert: Schlagworte wie Verschulung oder Entwissenschaftlichung sind zu hören und Studierende stehen im Verdacht, ihr Studium eher als Credit-Point-Jagd denn interessengeleitet zu gestalten (z.B. Stegemann, 2007, o. S.; Schultheis, et al. 2008). Meist handelt es sich jedoch um anekdotischen Beschreibungen, bis auf wenige Ausnahmen fehlen empirisch belegte Erkenntnisse.1 Denn obschon Studierende seit langem Gegenstand der Forschung sind, ist bislang wenig darüber bekannt, wie sie den langfristigen Bildungsprozess eines ganzen Studiums gestalten. Vorwiegend wurde Lernen im engeren Sinne, das so genannte "Classroom Learning" untersucht (Aineley, 2008). Forschungsfokus. Die diesem Beitrag zugrunde liegende Studie nimmt diese Forschungslücke auf und untersucht Zielvorstellungen und Handlungsstrategien Studierender bei der Bewältigung ihres Studienalltags in unterschiedlichen Bologna-konformen Studienprogrammen. Im Einzelnen wird gefragt, (1) welche Vorstellungen und Wahrnehmungen das Handeln Studierender prägen und (2) welche programmspezifischen Kontextbedingungen die Herausbildung dieser handlungsleitenden Charakteristika beeinflussen. Als theoretischer Rahmen wurde die so genannte Kulturpsychologie herangezogen, die Handeln als Resultat einer Wechselwirkung von individuell-psychischen Merk-malen und sozio-kulturell vermittelten Vorstellungen versteht (Shweder, 1991; Bruner, 1990).
Keywords: Hochschulentwicklung; Studienprogramme; Curriculum Development; Higher Education; Faculty Development

" Nur" didaktisch oder auch strategisch?: Strukturelle Verankerung, Aufgaben-und Wirksamkeitswahrnehmungen hochschuldidaktischer Einrichtungen in Deutschland - Jenert, Tobias; Brahm, Taiga
Die Lehrpraxis an Hochschulen breitenwirksam und nachhaltig zu verbessern, gehört zu den schwierigsten Herausforderungen für die Hochschuldidaktik. Ein möglicher Weg besteht darin, als hochschuldidaktische Einrichtung stets mit Blick auf die Gesamtstrategie der Hochschule und Anspruchsgruppen in der Hochschulleitung und -administration zu agieren (Jenert & Brahm, 2010). Es stellt sich die Frage, welche Vorstellungen bezüglich der eigenen Aufgaben und der Wirksamkeit des eigenen Handels hochschuldidaktische Stellen in Deutschland haben. Mit einer Online-Befragung von Leitungspersonen im Bereich Hochschuldidaktik und -entwicklung in Deutschland konnten 35 Personen (72 angeschrieben) erreicht werden, wobei sich ein breiter Querschnitt verschiedener Einrichtungen ergab. Abgefragt wurden (1) Struktur und institutionelle Anbindung der Einrichtung, (2) Wahrnehmung der eigenen Wirksamkeit sowie (3) Aufgabenschwerpunkte und notwendige Kompetenzen. Die Ergebnisse zeigen, dass einerseits ein Bewusstsein für Herausforderungen jenseits didaktischer Aus- und Weiterbildung besteht und die strategische Dimension erkannt ist. Gleichzeitig zeigt die Betonung "traditioneller" Aufgaben und Kompetenzen, dass die strategische Dimension im Tagesgeschäft oft noch keine zentrale Rolle spielt.
Keywords: Hochschulentwicklung; higher education development; Hochschuldidaktik

How to Assess and Study the Cultural Dimension of Social Interactions in Higher Education Institutions (HEI) - Gebhardt, Anja; Jenert, Tobias
Keywords: learning culture; social interaction

Institutionsweite Hochschulentwicklung als neo-institutionalistisches Phänomen - Brahm, Taiga; Gerholz, Karl-Heinz; Jenert, Tobias
Hintergrund / Kontext In der Hochschuldidaktik hat sich der traditionelle Ansatz, der sich auf das Individuum bezogene Aus- und Weiterbildungs- sowie Beratungsangebote konzentriert, weitgehend etabliert (Urban & Meister, 2010; Land, 2010; Dany, 2007). Allerdings sind diese Aktivitäten in Bezug auf die Bildungsqualität einer gesamten Hochschule oft wenig wirksam. Der Ansatz schlägt vor, hochschuldidaktische Initiativen auf mehreren Ebenen der Hochschule zu verankern: individuelle, programmbezogene und institutionelle Massnahmen (Jenert & Brahm, 2010; Brahm et al., 2010). Zielsetzung / Fragestellung Der Ansatz einer institutionsweiten Hochschulentwicklung wird vor dem Hintergrund einer aktuellen Erhebung zum Status Quo der Hochschuldidaktik diskutiert. Im Zentrum steht die Frage, wie, didaktische Initiativen in der Hochschule nachhaltig verankert werden können. Untersuchungsdesign / Datenerhebung und -auswertung In einer Online-Befragung wurden 32 Hochschuldidaktiker aus Deutschland und der Schweiz befragt. Zur Vertiefung wurden fünf telefonische Interviews durchgeführt. Die schriftlichen Befragungsdaten wurden mittels SPSS, die Interviews (nach der Transkription) inhaltsanalytisch ausgewertet. Erste Ergebnisse Die meisten hochschuldidaktischen Einrichtungen konzentrieren sich auf die Organisation und Durchführung von Qualifizierungsmassnahmen (für 71,9% der Befragten gehört dies zu den bedeutsamen Aufgaben). Dagegen wird die Unterstützung von Programmverantwortlichen oder der Hochschulleitung nur von einem Viertel der Befragten als wichtige Aufgabe erachtet. In den Interviews wird deutlich, dass nur wenige Ansätze bestehen, wie didaktische Initiativen in die gesamte Hochschule getragen werden können. Berufs- und wirtschaftspädagogische Relevanz Die ersten Ergebnisse der Untersuchung zeigen, dass das Feld der Hochschuldidaktik und -entwicklung bisher noch wenig strukturiert ist. Bestehende Ansätze der Berufs- und Wirtschaftspädagogik (z. B. Euler & Sloane, 1999; Gerholz et al., 2010; Gerholz, 2012) können einen Beitrag dazu leisten, didaktische Veränderungsinitiativen innerhalb der Hochschulen wirksamer und nachhaltiger zu gestalten.
Keywords: Hochschuldidaktik; Hochschulentwicklung; Neo-Institutionalismus; Strategie

Programmgestaltung als professionelle Aufgabe der Hochschulentwicklung: Gestaltungsmodell und Fallstudie - Jenert, Tobias (Einführung in die Studiengangentwicklung)

Studierende (als) Kunden?: Zum Umgang mit einer herausfordernden Beziehung zwischen Lehrenden und Lernenden - Jenert, Tobias; Fust, Alexander (Lernendenorientierung: Studierende im Fokus)

Service - Forscher - Change Agents?! Rollen und Strategien einer gestaltungsorientierten Hochschulentwicklung: Keynote-Vortrag im Rahmen des Jungen Forums Hochschul-und Mediendidaktik - Jenert, Tobias

An iterative plug-in algorithm for decomposing seasonal time series using the Berlin Method - Feng, Yuanhua (Journal of Applied Statistics)

Optimal convergence rates in non-parametric regression with fractional time series errors - Feng, Yuanhua; Beran, Jan (Journal of Time Series Analysis)

Filtered Log-Periodogram Regression of Long Memory Processes - Feng, Yuanhua; Beran, Jan (Journal of Statistical Theory and Practice)

Weighted Averages and Local Polynomial Estimation for Fractional Linear ARCH Processes - Beran, Jan; Feng, Yuanhua (Journal of Statistical Theory and Practice)

Weighted Averages and Local Polynomial Estimation for Fractional Linear ARCH Processes - Beran, Jan; Feng, Yuanhua (Journal of Statistical Theory and Practice)

Locally Weighted Autoregression - Feng, Yuanhua; Heiler, Siegfried (Econometrics in Theory and Practice)

A Multivariate Random Walk Model with Slowly Changing Drift and Cross-correlation Applied to Finance - Feng, Yuanhua; Hand, David; Yu, Keming

A review of event formats as enablers of event-driven BPM - Becker, Jörg; Matzner, Martin; Müller, Oliver; Walter, Marcel (Lecture Notes in Business Information Processing)
Event-driven Business Process Management (EdBPM) is based upon exchanging and processing business events. As yet, no commonly adopted event format for communicating business events between distributed event producers and consumers has emerged. This paper is an effort to review the status quo of event formats against the requirements of EdBPM. We particularly discuss BPAF, CBE, and XES as promising candidates and identify prospects for development.
Keywords: EDA; Event Exchange Format; edBPM

Extending BPMN for business activity monitoring - Friedenstab, Jan Philipp; Janiesch, Christian; Matzner, Martin; Müller, Oliver (Hawaii International Conference on System Sciences)
Real-time access to key performance indicators is necessary to ensure timeliness and effectiveness of operational business processes. The concept of Business Activity Monitoring (BAM) refers to the observation, analysis, and presentation of real-time information about business activities across systems' and companies' borders. Designing and maintaining BAM applications is challenging, as the involved concepts (e.g., business processes, audit logs, performance measures) --though being strongly interrelated-- are developed by different communities of practice. Also, they reside on different levels of abstraction, and are handled by different IT systems. Hence, we developed a conceptual modeling language which extends the widely accepted Business Process Modeling Notation (BPMN) by BAM-relevant concepts. The main results presented in this paper are: (1) a meta-model which formally describes the conceptual aspects of the developed BPMN extension (abstract syntax); (2) graphical symbols as an exemplary representation of this abstract syntax (concrete syntax); (3) a demo scenario that illustrates the application of the language in a fictitious scenario.

Beyond process monitoring: A proof-of-concept of event-driven business activity management - Janiesch, Christian; Matzner, Martin; Müller, Oliver (Business Process Management Journal)
Purpose – The purpose of this paper is to show how to employ complex event processing (CEP) for the observation and management of business processes. It proposes a conceptual architecture of BPM event producer, processor, and consumer and describes technical implications for the application with standard software in a perfect order scenario. Design/methodology/approach – The authors discuss business process analytics as the technological background. The capabilities of CEP in a BPM context are outlined an architecture design is proposed. A sophisticated proof-of-concept demonstrates its applicability. Findings – The results overcome the separation and data latency issues of process controlling, monitoring, and simulation. Distinct analyses of past, present, and future blur into a holistic real-time approach. The authors highlight the necessity for configurable event producer in BPM engines, process event support in CEP engines, a common process event format, connectors to visualizers, notifiers and return channels to the BPM engine. Research limitations/implications – Further research will thoroughly evaluate the approach in a variety of business settings. New concepts and standards for the architecture's building blocks will be needed to improve maintainability and operability. Practical implications – Managers learn how CEP can yield insights into business processes' operations. The paper illustrates a path to overcome inflexibility, latency, and missing feedback mechanisms of current process modeling and control solutions. Software vendors might be interested in the conceptualization and the described needs for further development. Originality/value – So far, there is no commercial CEP-based BPM solution which facilitates a round trip from insight to action as outlines. As major software vendors have begun developing solutions (BPM/BPA solutions), this paper will stimulate a debate between research and practice on suitable design and technology.
Keywords: Architecture; Business activity monitoring; Business process management; Business process re-engineering; Complex event processing; Computer software; Standard software

The demand for individual grievance procedures in Germany and Spain: Labour law changes versus business cycle - Frick, Bernd; Ocaña, Miguel Ángel Malo; Martinez, Pilar Garcia; Schneider, Martin (Estudios de economia aplicada)

Who owns the customer? Disentangling customer loyalty in indirect distribution channels - Eggert, Andreas; Henseler, J{\; Hollmann, Sabine (Journal of Supply Chain Management)

‘It's almost like taking the sales out of selling’—towards a conceptualization of value-based selling in business markets - Terho, Harri; Haas, Alexander; Eggert, Andreas; Ulaga, Wolfgang (Industrial Marketing Management)

Individuelle Förderung und berufliche Orientierung im berufsschulischen Übergangssystem - Ergebnisse aus dem Forschungs- und Entwicklungsprojekt InLab

Funktionen und Erträge pädagogischer Diagnostik im wirtschafts- und berufspädagogischen Bereich - Tramm, T.; Seeber, S.; Kremer, H.-Hugo (bwp@ Berufs- und Wirtschaftspädagogik - online)

Akademisierung der Berufsbildung - Büchter, K.; Frommeberger, D.; Kremer, H.-Hugo (bwp@ Berufs- und Wirtschaftspädagogik - online)

Origin of gate hysteresis inp-type Si-doped AlGaAs/GaAs heterostructures - Burke, A. M.; Waddington, D. E. J.; Carrad, D. J.; Lyttleton, R. W.; Tan, H. H.; Reece, P. J.; Klochan, O.; Hamilton, A. R.; Rai, A.; Reuter, Dirk; Wieck, A. D.; Micolich, A. P. (Physical Review B)

Magnetic field dependence of the spin relaxation length in spin light-emitting diodes - Höpfner, Henning; Fritsche, Carola; Ludwig, Arne; Ludwig, Astrid; Stromberg, Frank; Wende, Heiko; Keune, Werner; Reuter, Dirk; Wieck, Andreas D.; Gerhardt, Nils C.; Hofmann, Martin R. (Applied Physics Letters)

Hole spin precession in a (In,Ga)As quantum dot ensemble: From resonant spin amplification to spin mode locking - Varwig, S.; Schwan, A.; Barmscheid, D.; Müller, C.; Greilich, A.; Yugova, I. A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Transverse rectification in density-modulated two-dimensional electron gases - Ganczarczyk, A.; Rojek, S.; Quindeau, A.; Geller, M.; Hucht, A.; Notthoff, C.; König, J.; Lorke, A.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Momentum matching in the tunneling between 2-dimensional and 0-dimensional electron systems - Beckel, Andreas; Zhou, Daming; Marquardt, Bastian; Reuter, Dirk; Wieck, Andreas D.; Geller, Martin; Lorke, Axel (Applied Physics Letters)

Non-resonant optical excitation of mode-locked electron spin coherence in (In,Ga)As/GaAs quantum dot ensemble - Schwan, A.; Varwig, S.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Applied Physics Letters)

Noise thermometry in narrow two-dimensional electron gas heat baths connected to a quasi-one-dimensional interferometer - Buchholz, Sven S.; Sternemann, Elmar; Chiatti, Olivio; Reuter, Dirk; Wieck, Andreas D.; Fischer, Saskia F. (Physical Review B)

Hyperfine interaction mediated exciton spin relaxation in (In,Ga)As quantum dots - Kurtze, H.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Photoluminescence lineshape features of carbon δ-doped GaAs heterostructures - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Journal of Physics: Condensed Matter)

Cyclotron-resonant exciton transfer between the nearly free and strongly localized radiative states of a two-dimensional hole gas in a high magnetic field - Bryja, L.; Jadczak, J.; Wójs, A.; Bartsch, G.; Yakovlev, D. R.; Bayer, M.; Plochocka, P.; Potemski, M.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Electron-nuclei spin coupling in GaAs—Free versus localized electrons - Huang, J.; Chen, Y. S.; Ludwig, A.; Reuter, Dirk; Wieck, A. D.; Bacher, G. (Applied Physics Letters)

Probing Single-Charge Fluctuations at aGaAs/AlAsInterface Using Laser Spectroscopy on a Nearby InGaAs Quantum Dot - Houel, J.; Kuhlmann, A. V.; Greuter, L.; Xue, F.; Poggio, M.; Gerardot, B. D.; Dalgarno, P. A.; Badolato, A.; Petroff, P. M.; Ludwig, A.; Reuter, Dirk; Wieck, A. D.; et al. (Physical Review Letters)